2022
DOI: 10.3389/fpubh.2022.958857
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Asian hate: Discordant reporting of race-based hate incidents and unfair treatment and association with measures of wellbeing

Abstract: BackgroundDuring COVID-19, anti-Asian discrimination increased in attention. Hate and unfair treatment are related but do not completely overlap. We expect those who report a hate incident would also report race-based unfair treatment, yet feelings of social desirability or self-blame may lead to under-reporting of unfair treatment.ObjectivesTo describe reporting of an experience of race-based hate but not an experience of race-based unfair treatment among Asians in California and explore the association betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…The health effects reported by our participants encompass emotional, mental, and physical health effects. Our results align with findings from both regionally and nationally representative surveys and demonstrate the negative association between discrimination and well-being ( 8 , 21 , 22 ). A cross-sectional study that surveyed Chinese and South Asian adults in Chicago found that the prevalence of depressive symptoms among these groups had doubled since the pandemic began ( 23 ).…”
Section: Discussionsupporting
confidence: 89%
“…The health effects reported by our participants encompass emotional, mental, and physical health effects. Our results align with findings from both regionally and nationally representative surveys and demonstrate the negative association between discrimination and well-being ( 8 , 21 , 22 ). A cross-sectional study that surveyed Chinese and South Asian adults in Chicago found that the prevalence of depressive symptoms among these groups had doubled since the pandemic began ( 23 ).…”
Section: Discussionsupporting
confidence: 89%
“…Participants who identified their national origin as Asian Indian were categorized as "South Asian" (n = 10,789, 16.58%); participants who identified their background as Chinese, Japanese, Korean, or any combination of the three were categorized as "East Asian" (n = 24,093, 37.01%); and participants who identified their background as Cambodian, Filipino, Hmong, Laotian, Vietnamese, or any combination of the five were categorized as "Southeast Asian" (n = 30,209, 46.41%). This categorization, reflecting geographic regions, is consistent with prior research (e.g., Ponce et al, 2022) and allowed us to retain students who selected multiple counties of origin within similar geographic regions (e.g., Japanese and Korean). We examined key demographic covariates and bias-based bullying experiences for differences by country of origin for each of the categorizations, and results indicated very small to small effect sizes for differences.…”
Section: Ethnicitymentioning
confidence: 71%
“…Another potential explanation for our findings that Asian Americans exhibited lower rates of screening reception for numerous cardiometabolic conditions and cancers is rooted in the racial and sociopolitical climate in the United States during the pandemic. Research finds that during the pandemic, Asian Americans reported increased stress and heightened awareness and experiences of racism and xenophobia that were associated with delayed health care utilization and avoidance of health care services altogether ( Ponce et al, 2022 , Ren and Feagin, 2021 , Yoo et al, 2009 Yoo et al, 2009). Thus, it is also possible that low screening levels among Asian Americans pre-pandemic may have been exacerbated by widespread fear that seeking health care during the pandemic would put them at greater risk of experiencing discrimination or violence.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the lack of population-level screening recommendations for prostate cancer, we include individuals between 40 and 75 in our analyses as the NHIS asks respondents about prostate cancer screening beginning at age 40. For colorectal cancer, the USPSTF recommends that all adults above age 45 be screened every 5–10 years ( Ponce et al, 2022 ). Similar to our prostate cancer screening analyses and based on the NHIS questionnaire, we include individuals between 40 and 75 in our colorectal cancer screening analyses as this reflects the age range for which the NHIS asks respondents to report colorectal cancer screening reception.…”
Section: Methodsmentioning
confidence: 99%